HUBUNGAN KADAR HbA1c DENGAN KADAR KREATININ SERUM PADA PENDERITA DIABETES MELITUS TIPE 2 DI RUMAH SAKIT PERTAMINA BINTANG AMIN HUSADA BANDAR LAMPUNG TAHUN 2022 - Zulfian; Anggunan; Vica Sukma; Syuhada (Medula, 2022)
Diabetes mellitus occurs due to disturbances in the body's metabolism that causes hyperglycemia and is associated with abnormalities of work and/or insulin secretion. One of the complications of type 2 diabetes mellitus is diabetic nephropathy which can be diagnosed early by measuring creatinine levels. Correlative analytic research with cross sectional method uses purposive sampling technique. The study sample consisted of 30 patients with type 2 diabetes with HbA1c levels <7% percentage (26.7%) and HbA1c levels 7% percentage (73.3%). For serum creatinine levels, serum creatinine values ​​were <1.1mg/dl percentage (23.3%) and serum creatinine values ​​1.1mg/dl percentage (76.7%). The results of the chi square test showed p value = 0.037 and odd ratio value (CI 95%) 6.3333 because the p value = 0.037 < 0.05 there was a relationship between HbA1c levels and serum creatinine levels in patients with type 2 diabetes. Odd ratio 6.3333 which means high HbA1c levels height 6.3 times higher is a factor in the increase in serum creatinine levels in patients with type 2 diabetes at Pertamina Bintang Amin Husada Hospital Bandar Lampung in 2022.